1992
DOI: 10.1029/92jd00062
|View full text |Cite
|
Sign up to set email alerts
|

Formation of OH radicals in the gas phase reactions of O3 with a series of terpenes

Abstract: The gas phase reactions of 0 3 with ethene, isoprene, and a series of monoterpenes have been investigated at 296 +-2 K and atmospheric pressure of air in the presence of cyclohexane at concentrations sufficient to essentially totally scavenge any OH radicals formed. The expected products of the OH radical-initiated reaction of cyclohexane, cyclohexanone and cyclohexanol, were observed in all cases. From a knowledge of the chemistry of cyclohexane in these reaction systems and as a result of cyclohexanone and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
336
4
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(373 citation statements)
references
References 61 publications
31
336
4
2
Order By: Relevance
“…The concentration of nitrate increased rapidly at the beginning of the reaction and reached a maximum after ∼1 h. During the first 2 h of reaction, TMB and NO decayed exponentially (Figure 3c and d), suggesting that the majority of ON molecules were formed within 2 h of the start of the reaction. Decay rates of TMB and NO for dry and humid experiments were similar (except for the lower decay rates observed on 28 March with RH of ∼85%, for which the reason is not clear), which is consistent with the fact that water vapor has no effects on OH radical formation (Atkinson et al 1992) at the wavelengths of light (centered at 340 nm) employed in this study. In addition, it has been shown that the reaction of RO 2 and NO (reaction (1)) is not affected by RH (Matsunaga and Ziemann, 2009).…”
Section: Resultssupporting
confidence: 72%
“…The concentration of nitrate increased rapidly at the beginning of the reaction and reached a maximum after ∼1 h. During the first 2 h of reaction, TMB and NO decayed exponentially (Figure 3c and d), suggesting that the majority of ON molecules were formed within 2 h of the start of the reaction. Decay rates of TMB and NO for dry and humid experiments were similar (except for the lower decay rates observed on 28 March with RH of ∼85%, for which the reason is not clear), which is consistent with the fact that water vapor has no effects on OH radical formation (Atkinson et al 1992) at the wavelengths of light (centered at 340 nm) employed in this study. In addition, it has been shown that the reaction of RO 2 and NO (reaction (1)) is not affected by RH (Matsunaga and Ziemann, 2009).…”
Section: Resultssupporting
confidence: 72%
“…Similar to that observed for the ozonolysis of α-pinene, the observed interference measured with the addition of C 3 F 6 accounted for approximately 40 % of the observed signal in the absence of C 3 F 6 . When the measured interference was subtracted from the overall signal, the measured OH concentrations results in an overall OH yield of approximately 0.40 ± 0.01, which is in good agreement with the value reported by Atkinson et al (1992) of 0.35 ± 0.05. The percentage of interference as well as the resulting OH yield was relatively constant for each β-pinene concentration used; however, the results suggest that the OH yield may increase with increasing concentrations of β-pinene.…”
Section: Ozonolysis Experimentssupporting
confidence: 78%
“…That study used OH yields for β-caryophyllene (6%), which are at the low end of the reported range for OH yields from sesquiterpenes (e.g. Atkinson et al, 1992;Shu and Atkinson, 1994). Our observations suggest the OH yields are much higher, and that enhanced within-canopy reactivity might be a general characteristic of pine forests and other ecosystems where very reactive terpene emissions are substantial.…”
Section: Discussionmentioning
confidence: 98%